Relationship coach-athlete : outstanding trends in european research - Serpa, Sidónio Olivério da Costa (2009)
Sports performance, although depending on individuais'characteristics,also reflects the way coach-athlete relationship takes place in the sport preparation process. Social psychology of sport has developed the study of the interaction processes between those actors,aiming at having a better understanding of them and at having a conceptual basis to propose the management of that relationship in order to make it more productive in terms of social and sport dynamics. International research has been following difterent approaches in the study of this subject: (1) the social-emotional approach has been pointing out to the emotional component resulting from the interaction between coach and athlete, which may have both positive, or negative effects on the athlete's adapting behaviours, as well as on the affective balance of the dyad. Empirical research on satisfaction, drop out, self-esteem or self-efficacy are some examples of research topics in this field, as well as those produced within the scope of analytical psychology models; (2) the organisational approach takes into account the concept that sport teams are organisations that despite having specific characteristics, can be studied according to the models of organisational psychology. Thus, the relationship coach-athlete is studied under the leader-member perspective. Chelladurai's Multidimensional Model of Leadership in Sport considers the antecedents and consequences of leader's intervention, as well as the behaviours developed by him/her. It has been the most productive model regarding international research; (3) the behavioural approach has been investigating the coach's concrete behaviours in training or competition by means of observational methodologies, inspired by Smoll's & Smith's Mediational Model, which classifies the coach's behaviours in interactional categories. Therefore, the coach will be able to evaluate his/her effect upon the athlete and to introduce the needed changes in his/her behaviour. This article discusses these models referring to the main results in international research and also presents a model of coach's anxiogenic behaviours in the context of the sport training process.